PENGEMBANGAN MODEL PEMBELAJARAN STEAM PAUD BERBASIS SIBERNETIK - Saabighoot, Yus Alvar; Suminar, Uum; Hisyam, Mohamad (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Terbuka, 2023)
Learning Model Learning programs in science and technology, engineering, art, mathematics, cybernetic-based early childhood education have positive implications for learning activities, early childhood in the current era of early childhood disruption must be trained to have the ability to think critically, think creatively, collaborate and be able to communicate, the purpose of this development research wants to know the effectiveness of learning in early childhood using a learning model Cybernetic-based ECCE STEAM, the second is to want to know early childhood learning outcomes using the Cybernetic-Based ECCE STEAM learning model. Research and development was chosen as the research methodology with teacher respondents and children aged 5-6 years. Based on the results of research data analysis, it can be concluded that there is an increase in the effectiveness of early childhood in learning and an increase in teacher knowledge in implementing cybernetic-based ECCE STEAM learning. This model can be used as an alternative model to teach the basics of digital literacy and as digitization in the learning process as a catalyst for future education.